The effectiveness of transdermal iron patches in athletes with suboptimal iron status (Part 2) - McCormick, R.; Dawson, B.; Sim, M.; Lester, L.; Goodman, C.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The authors compared the effectiveness of daily (DAY) versus alternate day (ALT) oral iron supplementation in athletes with suboptimal iron. Endurance-trained runners (nine males and 22 females), with serum ferritin (sFer) concentrations <50 µg/L, supplemented with oral iron either DAY or ALT for 8 weeks. Serum ferritin was measured at baseline and at fortnightly intervals. Hemoglobin mass (Hbmass) was measured pre- and postintervention in a participant subset (n = 10). Linear mixed-effects models were used to assess the effectiveness of the two strategies on sFer and Hbmass. There were no sFer treatment (p = .928) or interaction (p = .877) effects; however, sFer did increase (19.7 µg/L; p < .001) over the 8-week intervention in both groups. In addition, sFer was 21.2 µg/L higher (p < .001) in males than females. No Hbmass treatment (p = .146) or interaction (p = .249) effects existed; however, a significant effect for sex indicated that Hbmass was 140.85 g higher (p = .004) in males compared with females. Training load (p = .001) and dietary iron intake (p = .015) also affected Hbmass. Finally, there were six complaints of severe gastrointestinal side effects in DAY, but only one in ALT. In summary, both supplement strategies increased sFer in athletes with suboptimal iron status; however, the ALT approach was associated with lower incidence of gastrointestinal upset.